RESULTS OF THE ON-LINE QUESTIONNAIRE OF STUDENTS OF FOREIGN CITIZENS’TRAINING DEPARTMENT ON CLINICAL ANATOMY AND OPERATIVE SURGERY REGARDING TECHNICAL SUPPORT OF EDUCATIONAL PROCESS AT DISTANCE LEARNING - Kavyn, V. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
The educational process in higher educational institutions of Ukraine is subject to reform and improvement, with the aim of forming a modern competitive specialist in the labor market. Higher medical education on the present stage requires the use of the hindmost technologies and tools during practical classes and lectures, methods of motivating students. The real challenge to the educational process was the COVID-19 pandemic, which contributed to a more active transition to distance learning in educational medical schools. Distance learning is one of the priority tasks of modern education. Electronic control, which is carried out during distance learning, has both advantages and disadvantages. Its main advantages include: the ability to quickly test the knowledge of a large number of students at the same time, improving the teacher’s professional skills, increasing the ability to implement individual work with students of higher education. Among the disadvantages of distance learning are: reduced language contact between the student and the teacher; the advantage of standardized thinking; the labor-intensive of the process, which is associated with the additional formating of the educational complex. Successful practical training in distance learning depends on proper technical support, mainly from students. During practical classes with foreign students, technical problems were repeatedly noted, which disrupted the educational process. This was the purpose of conducting a questionnaire of students to study their technical support to carry out the distance learning process.